Resistance to hegemonic nationalist discourse in Sean O’Casey’s dramaturgy - Sousa, Raimundo Expedito dos Santos (2019)
In order to prove the virility of Irish men, underestimated by the British Empire, anticolonial nationalism entailed a temporary suspension of the civil masculinity code in favor of the civic masculinity code, in which the heteroerotic romance was to be outlawed for the benefit of the nation. Sean O’Casey, divergent from this ideology promoted by the nationalist theatre, focuses on his works the neglect of the woman-flesh in favor of the woman-symbol. By examining the play The Plow and the Stars, this paper examines how the playwright deconstructs the sacrificial myth in that he denounces the pathologization of nationalism as collective hysteria resulting from the interdiction of Eros.